Participação do Hormônio Concentrador de Melanina (MCH) no hipotálamo lateral/área perifornicial (LH/PFA) e locus coeruleus (LC) na resposta ventilatória à hipercapnia em ratos durante o sono e vigília - Rodrigues, Laísa Taís Cabral (2020)
The melanin-concentrating hormone (MCH), a neuropeptide produced by neurons of a few areas in the CNS including the lateral hypothalamus/perifornical area (LH/PFA), has been implicated in the central hypercapnic chemoreflex, but the mechanisms involved have not been studied yet. Here, we evaluated whether MCH modulates the central chemoreflex acting in the LH/PFA and/or in the locus coeruleus (LC). For this, unanesthetized Wistar rats were microinjected with MCH [0.4 mM] into the LH/PFA and LC, and the MCH1-R antagonist SNAP-94847 [63 mM], into the LH/PFA, while the pulmonary ventilation was evaluated in room air and 7% CO2 together with body temperature, EEG and EMG, during wakefulness and sleep, in the dark and light periods. MCH intra-LH/PFA caused a decreased CO2 ventilatory response during wakefulness and sleep, in the light, but not in the dark period while SNAP-94847 intra-LH/PFA caused an increased CO2 ventilatory response during wakefulness in the light period. In the LC, MCH caused no change in the hypercapnic ventilatory response of rats. Our results suggest that MCH via MCH1-R in the LH/PFA, but not in the LC, exerts an inhibitory modulation of the hypercapnic ventilatory during the light-inactive period.